(3WHbGJ abgGA LHGd Gdjef hYjhf ef CNHGQ SGOGJ QDSGA GdRef heYQaI CfSGHge heHdZ CYeGQge hhbJ haGJges - (3YeQ Hf Ydj Hf SeQI Hf GdMSjf GdLYOj,J (B586 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CdgefG HMeOg s
(3BNQgG (B:s
(3Je cJGH WHbGJ GdabgGA ai LHGd Gdjef ef UfYGA Edi YOf Hefg hYhfg s
(3cJHJ HNW fSN bQjH ef GdJYdjbs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B55s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B676 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B173 s
Keywords: (3GdJGQjNs